Faktor-Faktor yang Memengaruhi Keputusan Pembelian Produk Asuransi Syariah: Perspektif Marketing Mix Dimoderasi Perilaku Rasulullah - Ali, Saiful; Busnetty, Ida (ARBITRASE: Journal of Economics and Accounting, 2026)
Islamic insurance is one of the financial products that is becoming increasingly popular in Indonesia, especially among communities that prioritize Sharia principles in every aspect of their lives. This study aims to analyze the influence of the marketing mix comprising product, price, promotion, and place on purchasing decisions for Islamic insurance products, as well as to examine the role of the implementation of the Prophet Muhammad’s (Rasulullah’s) behavior as a moderating variable in strengthening these relationships. The research method employs a quantitative approach using primary data obtained through questionnaires distributed to customers of PT Asuransi Askrida Syariah in the Jakarta metropolitan area. This study employs a quantitative research approach with proportional random sampling. Based on the predetermined criteria, 265 respondents were obtained, and data analysis was conducted using SmartPLS 4.0 software. The results indicate that the marketing mix variables product, price, place, and promotion have a positive and significant effect on purchasing decisions for Islamic insurance products. Among these variables, price has the largest path coefficient and is therefore identified as the most dominant factor influencing purchasing decisions. Furthermore, the implementation of Rasulullah’s behavior is proven to significantly moderate the effects of product and price on purchasing decisions, indicating that values of honesty, trustworthiness, and fairness strengthen consumers’ perceptions of product quality and price fairness. However, the implementation of Rasulullah’s behavior does not significantly moderate the effects of place and promotion on purchasing decisions, suggesting that these relationships are more influenced by consumers’ practical and functional considerations.